Implementation of TF-IDF Algorithm to detect Human Eye Factors Affecting the Health Service System - Sudarma, Made; Sulaksono, Juli (Universitas Nusantara PGRI Kediri, 2020)
Elderly is someone whose age is around 60-74 years, at that age, one's health tends to decrease, and it has an impact on reduced perception, cognition, and psychometry. One result of cognitive decline is a decrease in memory. Programs have been provided by the Indonesian government, such as submitting information, producing brochures, and making announcements on the health services website. But this counseling is not optimal because the elderly tend to be lazy to read this because the eyes have begun to look away from other than that the eye health of the elderly has already started to decrease. So that the health information provided by the health department can be optimized, we try to make a model that is used to summarize an article so that the article is easily understood by the elderly. To summarize the article, this study uses the term frequency-inverse document frequency (TF-IDF) algorithm. By using the TF-IDF algorithm, it is hoped that the elderly will more easily read health articles. User Experience Questionnaire after the application of writing software summary is higher than before the application of writing software summary that is 25.27> 19.30.